PENGARUH PENGGUNAAN EDMODO DAN KEMAMPUAN GURU DALAM MENDESAIN BAHAN AJAR TERHADAP HASIL BELAJAR PAI - Anis Fasilah; Naf’an Tarihoran; Asep Saefurohman (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2021)
This study aims to determinne (1)The effect of the use of Edmodo on learning outcomes of Islamic Education . (2)The effect of the ability of teachers in designing teaching materials on the learning outcomes of islamic education. (3)The effect of the use of Edmodo and the ability of teachers to design teaching materials on learning outcomes of Islamic Education. This research used the factorial-experimental method with quantitative approach and used the multiple linear regression analysis technique. Technique that was used on the sampling prosess is purposive sampling on 98 students respondent. This research has shown the Edmodo use in SMAN and MAN Cilegon city on average 57,65 can be categorized as sufficient. While the teachers ability in designing teaching materials in SMAN and MAN Cilegon city on average 58,13 can be categorized as sufficient. For the student learning outcomes in SMAN and MAN Cilegon city has been seen for the posttest result on the average 89,95 and can be the great category. The results of this study indicate that there is a significant effect between the Edmodo use and Islamic teachers ability in designing teaching materials to students learning outcomes with the ‘t’ test of significance level 0,019<0,05. Then H0 is rejected and H1 is accepted simultaneously and the ‘f’ test of significance 0,000<0,05. And there is considerable influence between the Edmodo use and teachers ability in designing teaching materials to students learning outcomes with an adjusted R value squared of 0.540 or 54%.